A laboratory-scale experimental investigation on the reuse of a modified red mud in ceramic materials production. (28th February 2018) - Scribot, Cyril; Maherzi, Walid; Benzerzour, Mahfoud; Mamindy-Pajany, Yannick; Abriak, Nor-Edine
Highlights: The compressible stacking model makes it possible to optimize the granular structure. Mechanical properties of ceramics decrease with the increasing MRM content. Vacuum extrusion allows to have ceramic materials with higher mechanical characteristics. Firing temperatures play an important role on properties of ceramic products. Abstract: The management of bauxite residues causes serious environmental problems worldwide due to their physico-chemical particularities. In this research, a bauxite residue collected from Gardanne Alumina Plant (France), renamed modified red mud (MRM) after dewatering treatment, was investigated for its reuse in the making of ceramic materials such as roof tiles or bricks. After physico-chemico-mineralogical investigations, formulations were tested by substituting natural clays with MRM at rates ranging from 0 to 30% and applying two firing temperatures at 950 °C and 1015 °C. Ceramics samples were characterized for their chemical, mineralogical, and mechanical properties. It was found that the addition of up to 30 wt% of the MRM allows the production of acceptable ceramic products such as tiles.